2012
DOI: 10.1039/c2cp22694d
|View full text |Cite
|
Sign up to set email alerts
|

Understanding solvent effects in the selective conversion of fructose to 5-hydroxymethyl-furfural: a molecular dynamics investigation

Abstract: Selective conversion of fructose to 5-hydroxymethyl-furfural (HMF) involves the participation of high-boiling solvents like dimethyl sulfoxide (DMSO). In order to replace DMSO with low-boiling solvents, it is imperative that we understand the effect of DMSO solvation in protecting (i) HMF from rehydration and humins formation reactions and (ii) fructose from side reactions, other than its dehydration to HMF. In the present work, molecular dynamics simulations of HMF and fructose in water and in water-DMSO mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
146
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 33 publications
(49 reference statements)
9
146
0
Order By: Relevance
“…74,86,89,90 Molecular dynamic investigation of fructose conversion into HMF in a DMSO/H 2 O solvent system has shown that DMSO competes with water in the solvation of both reactant and product. 78 DMSO acts as a hydrogen acceptor, interacting more effectively than water with hydrogen from hydroxyl groups in both fructose and HMF, while water can interact with the oxygen atom of the same hydroxyl groups. Therefore, the product yields tend to be higher in the presence of the aprotic solvent DMSO because: (i) its interaction with the fructose hydroxyl groups prevents deprotonation, and consequently, polymerization to undesirable products and (ii) its interaction with the HMF hydroxyl groups prevents rehydration, which could lead to the undesirable humins.…”
Section: Solvent Effect: More Than Only Dissolvingmentioning
confidence: 99%
See 2 more Smart Citations
“…74,86,89,90 Molecular dynamic investigation of fructose conversion into HMF in a DMSO/H 2 O solvent system has shown that DMSO competes with water in the solvation of both reactant and product. 78 DMSO acts as a hydrogen acceptor, interacting more effectively than water with hydrogen from hydroxyl groups in both fructose and HMF, while water can interact with the oxygen atom of the same hydroxyl groups. Therefore, the product yields tend to be higher in the presence of the aprotic solvent DMSO because: (i) its interaction with the fructose hydroxyl groups prevents deprotonation, and consequently, polymerization to undesirable products and (ii) its interaction with the HMF hydroxyl groups prevents rehydration, which could lead to the undesirable humins.…”
Section: Solvent Effect: More Than Only Dissolvingmentioning
confidence: 99%
“…Therefore, the product yields tend to be higher in the presence of the aprotic solvent DMSO because: (i) its interaction with the fructose hydroxyl groups prevents deprotonation, and consequently, polymerization to undesirable products and (ii) its interaction with the HMF hydroxyl groups prevents rehydration, which could lead to the undesirable humins. 78 Another important effect of DMSO is increasing the fructose dehydration reaction rate. It has been found that the slowest steps of the reaction involve intramolecular hydride transfer, requiring a reorganization of the polar solvent environment and the solvation of asymmetrically distributed electronic charges.…”
Section: Solvent Effect: More Than Only Dissolvingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that DMSO can promote dehydration efficiently, which could be attributed to the formation of strong acids from the thermolysis of DMSO in air such as sulfuric and methanesulfonic acids during the dehydration of fructose to 5-HMF, especially in high temperatures [25]. Moreover, DMSO would stabilize 5-HMF and suppress both the 5-HMF rehydration and the formation of condensation by-products because DMSO could prevent 5-HMF from rehydration to levulinic acid, formic acid, and humins by a preferential coordination of DMSO around the 5-HMF molecule, and protect the fructose molecule from reactions other than its dehydration to 5-HMF by a specific coordination of DMSO around the fructose molecule [26,27].…”
Section: The Firstmentioning
confidence: 99%
“…Moreover, DMSO would stabilize 5-HMF and suppress both the 5-HMF rehydration and the formation of condensation by-products because DMSO could prevent 5-HMF from rehydration to levulinic acid, formic acid, and humins by a preferential coordination of DMSO around the 5-HMF molecule, and protect the fructose molecule from reactions other than its dehydration to 5-HMF by a specific coordination of DMSO around the fructose molecule [26,27]. It was obvious that most of the fructose was converted after 1 h, and the reaction with SiO2-HNO3 was always able to obtain a higher final conversion and 5-HMF yield than it was without SiO2-HNO3, demonstrating that SiO2-HNO3 actually accelerated the reaction and promoted the production of 5-HMF, especially at low temperatures.…”
Section: The Firstmentioning
confidence: 99%